Psychological well-being of teachers: influence of burnout, personality, and psychosocial climate - Espinoza-Díaz, Ivette Margarita; Tous-Pallarés, Jordi; Lucas-Mangas, Susana; Valdivieso-León, Lorena; Vigil-Colet, Andreu (Frontiers in Psychology, 2023)
Those who are professionally dedicated to teaching can be exposed with their work to situations that influence their perception of psychological well-being. This study aims to evaluate how the factors of personality, emotional intelligence, burnout and the psychosocial climate derived from the work environment of teachers influence their levels of psychological well-being, to verify whether these variables allow us to establish a predictive model of psychological well-being by means of multiple regression analysis. Participants were a group of 386 teachers in early childhood, Primary and Secondary education, both in training and in active service (71.5% women; 28.5% men). A correlation and multiple regression analysis were performed to establish a predictive model of psychological well-being. We used 5 instruments: Psychosocial Climate at Work Scales (ECPT); Overall Personality Assessment Scale (OPERAS); Questionnaire for Evaluation of Burnout Syndrome at Work (CESQT); Spanish adaptation of the Riff Psychological Well-being Scales (EBP) and Spanish validation of the Trait Meta-Mood Scale (TMMS-24). Most of the relationships were significant, and the multiple regression analysis explains 58.5% of the global variance of psychological well-being in teachers, being emotional stability the most relevant and main predictor of psychological well-being, explaining its 38.1%. Personality shows a great influence in psychological well-being of teachers, particularly emotional stability. The ability to establish predictive models to explain psychological well-being in educational environments is confirmed.